Dual feedstock pyrolysis of Aegle marmelos pressed seed cake and novel Annona squamosa seed particles: the effect of dual natural antioxidant on the oxidation stability of derived co-pyrolysis liquid-A green approach. Issue 5 (28th May 2023) - Baranitharan, P.; Sriariyanun, Malinee; Babu, D.; Sakthivel, R.
Abstract: Numerous research programs are currently underway to introduce bio-fuel as a substitute for fossil fuels. At present, pyrolysis oil is used as a blend along with diesel but the usage of pyrolysis oil as a fuel in the engine is highly tedious because of its unstable nature. In this study, the stability of pyrolysis oil (ASTM D7467) is examined by adding 10% of Hibiscus rosasinesis (HRS) and 10% of green tea leaves (GTL) extracts as natural anti-oxidants. For the production of pyrolysis oil, co-pyrolysis of Aegle marmelos (AM) pressed seed cake and Annona squamosa (AS) seed particles was used (50:50 wt.%) as a new feedstock. Rancimat apparatus is used to analyze the oxidation stability index (OSI) of the raw co-pyrolysis oil and natural anti-oxidant doped co-pyrolysis oil. The OSI for the co-pyrolysis oil was improved to 3.97 h from 1.5 h by adding the HRS natural anti-oxidant extract, which met ASTM-D 6751 (American) standards. The GTL natural anti-oxidant extract was improved the OSI of co-pyrolytic liquid 6.45 h from 1.5 h, which is satisfied the both American and EN 14214 (European) standard. Hence, HRS and GTL extracts able to use as an eco-friendly anti-oxidant instead of synthetic anti-oxidants for enhancing the bio-fuel stability.